2018
DOI: 10.1158/1055-9965.epi-17-0671
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Urine 4-(Methylnitrosamino)-1-(3)Pyridyl-1-Butanol and Cotinine for Assessment of Active and Passive Smoke Exposure in Urban Adolescents

Abstract: Many adolescents are exposed to tobacco smoke, from either active smoking (CS) or secondhand smoke (SHS) exposure. Tobacco-specific biomarkers of exposure include cotinine (detects use in past 2-4 days) and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL; detects use for a month or longer). NNAL is expected to detect more intermittent tobacco exposure. We compared NNAL and cotinine as biomarkers of exposure to tobacco in urban adolescents and determined the optimal NNAL cutoff point to distinguish CS from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 31 publications
1
35
6
Order By: Relevance
“…The median urinary cotinine concentration measured in our participants who used pods was 244.8 ng/mL (IQR 8.4–1255.8), higher than 155.2 ng/mL (IQR: 68.8–579.2) reported by Benowitz et al in 55 adolescents (ages 13–19 years) who regularly smoked conventional tobacco cigarettes 6. All analysed samples had either undetectable or very low levels of the urinary tobacco-specific biomarker, NNAL, confirming lack of exposure to tobacco smoke.…”
Section: Resultscontrasting
confidence: 69%
“…The median urinary cotinine concentration measured in our participants who used pods was 244.8 ng/mL (IQR 8.4–1255.8), higher than 155.2 ng/mL (IQR: 68.8–579.2) reported by Benowitz et al in 55 adolescents (ages 13–19 years) who regularly smoked conventional tobacco cigarettes 6. All analysed samples had either undetectable or very low levels of the urinary tobacco-specific biomarker, NNAL, confirming lack of exposure to tobacco smoke.…”
Section: Resultscontrasting
confidence: 69%
“…Physiological evidence of high absorption of nicotine salt from JUUL pods was observed in a clinical study by Goniewicz and colleagues [78], who tested urinary cotinine levels, a biomarker of nicotine exposure, in 12-21 year olds who use podstyle devices on a regular basis. The study found that participants who used nicotine salt-containing devices had average urinary cotinine levels of 244.8 ng/mL, which is higher than a previous report of cotinine levels from 13 to 19 year olds (66-132 ng/mL), who regularly smoked tobacco cigarettes [79]. In our study, we found that JUUL crème brûlée aerosol contained low levels of carbonyls, including formaldehyde (0.053 µg/puff, Table 1), which is lower than levels previously reported for JUUL aerosols (0.07-0.50 µg/puff ) [73,76].…”
Section: Discussioncontrasting
confidence: 73%
“…NNAL has a half-life of 10–18 days and remains detectable for 6–12 weeks after combustible tobacco exposure 24. NNAL concentrations were normalised for creatinine25 and should not be present in levels above 10 pg/mg creatinine in adolescents with no recent active smoking and either past smoking or light secondhand smoke exposure (neither of which would be expected to significantly affect cotinine) 26. Saliva and urine samples were analysed at the Clinical Pharmacology Laboratory at the University of California, San Francisco.…”
Section: Methodsmentioning
confidence: 99%
“…Analyses were conducted in both the full sample (N=173) and in the subsample of e-cigarette only users (N=144). As described above, e-cigarette only users were defined as adolescents who reported no combustible cigarette use in the past 24 hours and had NNAL levels<10 pg/mL creatinine 26. Due to rapid changes in e-cigarette product availability and regulation, partial correlations were also examined, adjusting for date of assessment (ie, days passed from assessment date to present date).…”
Section: Methodsmentioning
confidence: 99%